A NEW SPECIES OF NEPENTHES (NEPENTHACEAE) FROM SUMATRA - Akhriadi, Pitra; Hernawati, Hernawati; Tamin, Rusjdi (Research Center for Biology, 2004)
AKHRIADI, PITRA, HERNAWATI & TAMIN, RUSJDI. 2004. A new species of Nepenthes(Nepenthaceae) from Sumatra. Reinwardtia 12 (2): 141 â 144. - A NewSpecies of Nepenthes rigidifolia is described.